Twin crowns - Doyle, Catherine (Paranormal fiction writer); Webber, Katherine, 1987- (Balzer + Bray, an imprint of HarperCollinsPublishers, 2023)
"Wren Greenrock has always known that one day she'd steal her sister's place on the throne. Trained from birth to return to the palace and avenge her parents' murder, she'll do anything to become queen and protect the community of witches who raised her. Or she would, if only a certain guard wasn't quite so distractingly attractive, and if her reckless magic would stop causing trouble. Princess Rose Valhart knows that with power comes responsibility--and she won't let a small matter like waking up in the desert with an extremely impertinent (and very handsome) kidnapper get in the way of her duty. But life outside the palace is wilder and more beautiful than she ever imagined, and the witches she has long feared might turn out to be the family she never had."--